Improved reconstruction of highly boosted [tau]-lepton pairs in the [tau][tau]→ ([mu][nu] [mu] [nu] [tau])(hadrons+[nu] [tau]) decay channels with the ATLAS detector - Aad, Georges; Ackermann, Anke; Baltes, Lisa Marie; Bartels, Falk; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Mkrtchyan, Tigran; Rassloff, Damir Fabrice; Sanfilippo, Lorenzo; Schöning, André; et al. (The European physical journal. C, Particles and fields, 2025)
This paper presents a new $$τ $$-lepton reconstruction and identification procedure at the ATLAS detector at the Large Hadron Collider, which leads to significantly improved performance in the case of physics processes where a highly boosted pair of $$τ $$-leptons is produced and one $$τ $$-lepton decays into a muon and two neutrinos ($$τ _μ $$), and the other decays into hadrons and one neutrino ($$τ _had$$). By removing the muon information from the signals used for reconstruction and identification of the $$τ _had$$candidate in the boosted pair, the efficiency is raised to the level expected for an isolated $$τ _had$$. The new procedure is validated by selecting a sample of highly boosted $$Z→ τ _μ τ _had$$candidates from the data sample of 140 $$fb^{-1}$$of proton-proton collisions at 13 TeV recorded with the ATLAS detector. Good agreement is found between data and simulation predictions in both the $$Z→ τ _μ τ _had$$signal region and in a background validation region. The results presented in this paper demonstrate the effectiveness of the $$τ _had$$reconstruction with muon removal in enhancing the signal sensitivity of the boosted $$τ _μ τ _had$$channel at the ATLAS detector.